2020
DOI: 10.1002/eat.23420
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder symptoms among adolescent boys and girls in Iran

Abstract: Objective: Few studies of eating disorder (ED) symptoms among young people in Iran have been conducted. This cross-sectional study examined ED symptoms, assessed by the Eating Disorder Examination Questionnaire (EDE-Q). Method: Adolescent boys (n = 498) and girls (n = 607) aged 12-19 years, recruited from schools in four different regions of Iran, completed a survey that included the EDE-Q. ED symptoms, namely, EDE-Q global scores and the occurrence of specific ED behaviors, were compared between boys and girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 27 publications
1
37
1
1
Order By: Relevance
“…Perhaps most alarmingly, Chua, Fitzsimmons-Craft, Austin, Wilfley, and Taylor (2021) studied the estimated prevalence of EDs in Singapore, reporting that while approximately 6% screened positive for a clinical ED, a further 37% screened positive for other specified feeding or eating disorder, and another 19% were at high risk for developing an ED. Interestingly, there were few gender differences in the estimated prevalence of EDs and ED behaviors in Singapore (Chua et al, 2021) or Iran (Sahlan, Saunders, Mond, & Fitzsimmons-Craft, 2021b).…”
Section: Prevalencementioning
confidence: 99%
“…Perhaps most alarmingly, Chua, Fitzsimmons-Craft, Austin, Wilfley, and Taylor (2021) studied the estimated prevalence of EDs in Singapore, reporting that while approximately 6% screened positive for a clinical ED, a further 37% screened positive for other specified feeding or eating disorder, and another 19% were at high risk for developing an ED. Interestingly, there were few gender differences in the estimated prevalence of EDs and ED behaviors in Singapore (Chua et al, 2021) or Iran (Sahlan, Saunders, Mond, & Fitzsimmons-Craft, 2021b).…”
Section: Prevalencementioning
confidence: 99%
“…Although once thought to be an exclusively Western phenomenon, research over the past two decades highlights the severity of ED symptoms and ED symptoms clinical impairment among children, adolescents and college samples in Iran [37][38][39][40][41][42][43][44]. Within the Iranian context, there are some similarities and differences in ED symptoms across sex [41,42]. For example, adolescent girls had higher dietary restriction compared with boys; however, probable ED symptoms, binge and purge behaviors were comparable across sex [41].…”
Section: Eating Disorder Symptoms In Iranmentioning
confidence: 99%
“…Within the Iranian context, there are some similarities and differences in ED symptoms across sex [41,42]. For example, adolescent girls had higher dietary restriction compared with boys; however, probable ED symptoms, binge and purge behaviors were comparable across sex [41]. Another study on children and adolescents, aged 6-18, indicated that with exception of other EDs, binge eating disorder (BED) was higher in boys than girls [37].…”
Section: Eating Disorder Symptoms In Iranmentioning
confidence: 99%
“…The latter is explained by the following multifactorial determinants: (1) physiological factors related to adolescence and a greater increase in adipose tissue among girls during this period and (2) psychological factors related to females sharing a greater need to compete and focus on their look and sexual appearance. Girls have a tendency to delay the puberty process by refusing to eat [ 11 ].…”
Section: Introductionmentioning
confidence: 99%